2017
DOI: 10.1039/c6fo01591c
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of Silibinin in combination with Pu-erh tea extract on non-alcoholic fatty liver disease in ob/ob mice

Abstract: There are presently no miracle drugs for non-alcoholic fatty liver disease (NAFLD). This study investigates the synergistic effect of Silibinin combined with Pu-erh tea extract (PTE) against NAFLD and explores the suggested mechanism of action. Ob/ob mice were fed a high fat diet along with the oral administration of Silibinin (86 mg per kg per day), PTE (250 mg per kg per day) or their combination for 6 weeks. Their lean littermates who were fed with standard chow diet were used as the control group. The bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Compounds. Tea polyphenol and its major component EGCG are commonly recognized as healthy and safe foods [193,194]. A double-blind randomized clinical trial on 45 NAFLD patients showed that daily received 550 mg of green tea tablets for 3 months significantly improved the body mass index, level of AST, and fasting blood sugar [195].…”
Section: Safety and Application Issue Of Teas And Their Bioactivementioning
confidence: 99%
“…Compounds. Tea polyphenol and its major component EGCG are commonly recognized as healthy and safe foods [193,194]. A double-blind randomized clinical trial on 45 NAFLD patients showed that daily received 550 mg of green tea tablets for 3 months significantly improved the body mass index, level of AST, and fasting blood sugar [195].…”
Section: Safety and Application Issue Of Teas And Their Bioactivementioning
confidence: 99%
“…(3) improving cholesterol homeostasis via regulating the mRNA expression of apolipoprotein B100 and ATP-binding cassette transporter A1; and (4) preventing gut dysbacteriosis [18,175,176].…”
Section: Hepato-protective Effect In Vivomentioning
confidence: 99%
“…In addition, CE combines with ApoB to form lipoproteins, which are transported outside the cell by exocytosis. Curcuma longa L., resveratrol, and PTE could significantly decrease the level of ApoB (Ramirez-Bosca et al, 2000;Tome-Carneiro et al, 2012;Hu et al, 2017). Celastrol was able to effectively suppress weight and attenuate highfat-mediated oxidative injury by improving ABCA1 expression, reducing the levels of TC, TG, LDL-c, and ApoB in the plasma, and increasing antioxidant enzyme activities and inhibiting nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity (Wang C. et al, 2014).…”
Section: Regulation Of Cholesterol Effluxmentioning
confidence: 99%
“…The expression of the reverse cholesterol transporters ABCA1 and ABCG1 was highly expressed in the livers of mice on pu-erh tea intervention ( Huang et al, 2019 ). Furthermore, apolipoprotein B100 (ApoB100) is a constitutive protein of LDL-c, and it was significantly downregulated by pu-erh tea extract (PTE) treatment ( Hu et al, 2017 ).…”
Section: Targeting Lipid Metabolism With Bioactive Compounds From Tcms With Anti-obesity Effectsmentioning
confidence: 99%